Evaluation of Seed Dormancy, One of the Key Domestication Traits in Chickpea - Veronika Sedláková (MDPI AG, 2021)
Legume seed dormancy has been altered during the domestication process, resulting in non-dormant seeds with a testa that is readily permeable for water. Ultimately, this provides fast and uniform germination, in contrast to dormant seeds of the wild progenitor. To date, germination and seed dormancy were studied mostly in relation to two types of cultivated chickpea: kabuli and desi. We studied seed dormancy, from physiological and anatomical perspectives, in chickpea crops and compared cultivated chickpeas to the wild chickpea progenitor and set of recombinant inbred lines (RIL). There was significant difference in the macrosclereid length of parental genotypes. Cultivated chickpea (C. arietinum, ICC4958) had mean of 125 µm, while wild C. reticulatum (PI48977) had a mean of 165 µm. Histochemical staining of the seed coat also showed differences, mainly in terms of Sudan Red detection of lipidic substances. Imbibition and germination were tested and several germination coefficients were calculated. Cultivated chickpea seeds imbibed readily within 24 h, while the germination percentage of wild chickpea at various times was 36% (24 h), 46% (48 h), 60% (72 h) and reached 100% only after 20 days. RIL lines showed a broader distribution. This knowledge will ultimately lead to the identification of the underlying molecular mechanism of seed dormancy in chickpea, as well as allowing comparison to phylogenetically related legumes, such as pea, lentil and faba bean, and could be utilized in chickpea breeding programs.